2012
DOI: 10.1080/10810730.2012.666623
|View full text |Cite
|
Sign up to set email alerts
|

Building a National Model for Knowledge Exchange in Malawi: Findings From a Health Information Needs Assessment

Abstract: Getting the right information into the right hands at the right time is a challenge for many health systems in developing countries. Health workers need access to reliable and up-to-date health information in order to support their clients. This health information needs assessment, conducted in the capital city and 3 districts of Malawi from July 2009 to September 2009, aimed to determine access to, and need for, health information in HIV/AIDS and family planning/reproductive health at all levels of the health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 8 publications
3
21
0
Order By: Relevance
“…The major identified reasons for low usage of computers in the study included the limited access to computer systems, high computer illiteracy rate and lack of time. Similar results were found in other studies . So, there is a need to provide ICT infrastructure, training regarding their usage and a conducive environment for their use so that information should reach the community health workers.…”
Section: Implications For Policy and Practicesupporting
confidence: 80%
See 1 more Smart Citation
“…The major identified reasons for low usage of computers in the study included the limited access to computer systems, high computer illiteracy rate and lack of time. Similar results were found in other studies . So, there is a need to provide ICT infrastructure, training regarding their usage and a conducive environment for their use so that information should reach the community health workers.…”
Section: Implications For Policy and Practicesupporting
confidence: 80%
“…A study conducted in Pakistan also reported broadcast media, especially television, as a credible source of health information for health workers . Similarly, in a study conducted in Malawi, face‐to‐face communication was found to be the most preferred method of sharing knowledge and information among health workers . However, one of the studies noted that discussion with colleagues (2.7%) for provision of health information was poorly practiced as compared to books, protocol manuals, training sessions and the Internet .…”
Section: Discussionmentioning
confidence: 53%
“…An assessment of health information needs conducted early in the K4Health Malawi project showed that in Nkhotakota and Salima Districts, these frontline workers often lacked essential up-to-date knowledge about the health areas for which they were responsible 11 . Although there was frequent communication and knowledge exchange between national and district levels, this did not hold true between districts and communities.…”
Section: Introductionmentioning
confidence: 99%
“…Mobile phone towers exist throughout Malawi, and some service providers own mobile phones and use them for both short message service (SMS) text messages and voice calls 11 . Although very few CHWs in Nkhotakota and Salima Districts personally owned and used mobile phones at the time of the needs assessment, project staff agreed that the large and growing use of the SMS technology offered great potential as a channel for knowledge exchange.…”
Section: Introductionmentioning
confidence: 99%
“…Health systems and sub-systems research includes health systems frameworks [60,61], health systems management [62,63], health systems strengthening [13,17,21], health systems evaluation [48,64], accessibility, equality and efficiency of health systems [65-67], primary care system [68], public health systems [69-71], and mental health systems [72-74]. Healthcare and services research (i.e., Brazil) include accessibility, equality and efficiency of healthcare [75,76], primary healthcare and mental healthcare [49,73,74,77-79], managed care and integrated care [80-82], healthcare innovation [83,84], health care delivery models [85,86], responsiveness to health services [53,87], influencing demand for care [88,89], financial question of healthcare [48,90]. Health includes health measurement and evaluation [91,92], health promotion [93], health accessibility and equality [94-96].…”
Section: Resultsmentioning
confidence: 99%